“STICK-TO-ITTY”: USING ORAL LIFE HISTORIES IN PRINCEVILLE, NORTH CAROLINA, UNDERSTANDING PERCEPTIONS OF PRIDE, EMOTIONS, AND RESILIENCE IN THE AFTERMATH OF HURRICANES FLOYD AND MATTHEW - Evans, Kayla J (East Carolina University, 2021)
This thesis uses oral life histories conducted in Princeville, North Carolina, the oldest town chartered by Freed Blacks in the United States, to discuss community-engaged research and outreach, as well as resilience, in post-disaster context. Through oral life history interviews, we collected the experiences of Princeville residents with Hurricanes Floyd (1999) and Matthew (2016). Analysis of interview data revealed themes of pride, emotions, and resilience in the aftermath of devastation brought by historic floods. Drawing on anthropological, sociological, and historical methods, this thesis discusses these themes while exploring how connection to place, community resilience, and the lack of representation in the historical narrative of the United States play roles in a town's decision to rebuild or relocate.
Keywords: Oral Life Histories; natural disaster; Anthropology; Ethnographic; Hurricanes--Social aspects--North Carolina-- Princeville; Resilience (Personality trait); Hurricane Matthew, 2016--Social aspects; Hurricane Floyd, 1999--Social aspects; Princeville (N.C.)--History